Impact of Work Discipline on Increasing Employee Work Productivity - Nurul Amien Rosadisyam; Mahjudin , Mahjudin; Enny Istanti; Rina Dewi; Achmad Daengs GS (Journal of Economic and Business Advancement, 2026)
This study investigates the impact of work discipline on increasing employee work productivity within a corporate setting using an empirical quantitative approach. The research was conducted at PT. Wira Nusa Abadi Surabaya, employing a census method involving 55 employees as respondents. Data were collected through structured questionnaires measuring work discipline and employee productivity using Likert-scale indicators. Statistical analysis was performed using simple linear regression to estimate the functional relationship between discipline and productivity, supported by classical assumption testing to ensure model validity. The regression results indicate a positive coefficient of 0.540, suggesting that improvements in work discipline are associated with increased productivity levels. Hypothesis testing using a one-tailed t-test at a 0.05 significance level produced a calculated t-value of 3.507, exceeding the critical value of 2.006, thereby confirming statistical significance. These findings demonstrate that work discipline functions as a measurable determinant of employee productivity and provides empirical support for managerial policies emphasizing structured behavioral compliance to enhance organizational performance.